2007
DOI: 10.1242/jcs.009308
|View full text |Cite
|
Sign up to set email alerts
|

RANBP1 localizes a subset of mitotic regulatory factors on spindle microtubules and regulates chromosome segregation in human cells

Abstract: The GTPase RAN has an established role in spindle assembly and in mitotic progression, although not all mechanisms are fully understood in somatic cells. Here, we have downregulated RAN-binding protein 1 (RANBP1), a RAN partner that has highest abundance in G2 and mitosis, in human cells. RANBP1-depleted cells underwent prolonged prometaphase delay often followed by apoptosis. Cells that remained viable assembled morphologically normal spindles; these spindles, however, were hyperstable and failed to recruit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 52 publications
2
77
1
Order By: Relevance
“…Early apoptotic cells were identified from 4,6-diamidino-2-phenyl indole (DAPI) staining, revealing chromatin condensation, and immunofluorescence (IF) to lamin B1, which is cleaved during early apoptosis. We found a significant increase in apoptotic cells in cultures treated with RanBP1-specific siRNAs compared to GL2-interfered control cultures (Figure 1b), consistent with previous studies (Li et al, 2007;Tedeschi et al, 2007). We next stained the cells with a specific antibody for active caspase-3, an important regulator of apoptosis.…”
Section: Ranbp1 Interference In U2os Cells Results In Apoptosis Inducsupporting
confidence: 89%
See 4 more Smart Citations
“…Early apoptotic cells were identified from 4,6-diamidino-2-phenyl indole (DAPI) staining, revealing chromatin condensation, and immunofluorescence (IF) to lamin B1, which is cleaved during early apoptosis. We found a significant increase in apoptotic cells in cultures treated with RanBP1-specific siRNAs compared to GL2-interfered control cultures (Figure 1b), consistent with previous studies (Li et al, 2007;Tedeschi et al, 2007). We next stained the cells with a specific antibody for active caspase-3, an important regulator of apoptosis.…”
Section: Ranbp1 Interference In U2os Cells Results In Apoptosis Inducsupporting
confidence: 89%
“…Having previously found that RanBP1 downregulation yields hyperstable MTs and induction of apoptosis (Tedeschi et al, 2007), we sought to gain insight into the apoptotic machinery involved. To that aim we transfected U2OS osteosarcoma cells for 48 h with two smallinterfering RNA oligonucleotides (siRNAs, indicated as 202 and 459 in the map in Figure 1a) that specifically silence the RanBP1 gene, or with an siRNA targeting the nonhuman luciferase gene (GL2).…”
Section: Ranbp1 Interference In U2os Cells Results In Apoptosis Inducmentioning
confidence: 99%
See 3 more Smart Citations